THEORETICAL ASPECTS OF SPEED-STRONG TRAINING OF SHORT-DISTANCE RUNNERS - Утепбергенова Айсара (Web of Journals Publishing, 2025)
Based on the theoretical analysis of the data of scientific and methodological literature, the main directions and features of the training of qualified short-distance runners are determined. It is established that the main condition for determining the content of training programs is the choice of the leading components of athletes' training.
Keywords: Sprinters, speed and strength training, runners, annual cycle, speed abilities.